Design Principles of Mobile Learning Module to Enhance English for Academic Survival Skills - Md. Ngadiran, Nurizah (Development in Language Studies, 2023)
‘Tutor Me’ was developed to assist low proficiency ESL learners who enrol in UHB 10302 course (English for Academic Survival) in Universiti Tun Hussein Onn Malaysia (UTHM) to develop their English for academic survival skills, which include effective reading, effective listening, paragraph writing and presentation skills. It is crucial for the targeted students to be assisted with a comprehensive module to be used during tutorial sessions and Independent Study Hours (ISH) sessions. As for Phase Two (Design and Development), one of the objectives is to construct the mLearning module design principles. The implication of this study focuses on the development of design principles to develop mLearning module to enhance English for academic survival skills.